Tanshinol suppresses endothelial cells apoptosis in mice with atherosclerosis via lncRNA TUG1 up-regulating the expression of miR-26a - Chen, Chao; Cheng, Guangqing; Yang, Xiaoni; Li, Changsheng; Shi, Ran; Zhao, Ningning (American journal of translational research, 2016)
Endothelial cell (EC) apoptosis is a crucial process for the development of atherosclerosis. Tanshinol is reported to protect vascular endothelia and attenuate the formation of atherosclerosis. However, the potential molecule mechanism of the protective role of tanshinol in atherosclerosis need to be further investigated. ApoE(-/-)mice were fed with a high-fat diet and treated with tanshinol to detect the effect of tanshinol on endothelial cells apoptosis with TUNEL staining assay. qRT-PCR and Western blot were performed to examine the expression of TUG1 and miR-26a in endothelial cells. RNA-binding protein immunoprecipitation assay was performed to verify the relationship between TUG1 and miR-26a. It has been shown that tanshinol reduced the aortic atherosclerotic lesion area in the entire aorta and aortic sinus in a concentration dependent manner, and suppressed the endothelial cells apoptosis in ApoE(-/-) mice. We further found that the mRNA level of TUG1 was reduced and the expression of miR-26a was up-regulated by tanshinol in endothelial cells. In addition, TUG1 down-regulated the expression of miR-26a in ECV304 cells. Finally, it was shown that overexpression of TUG1 removed the reversed effect of tanshinol on oxidized low-density lipoprotein (ox-LDL)-induced endothelial cells apoptosis. Taken together, our study reveals that tanshinol could attenuate the endothelial cells apoptosis in atherosclerotic ApoE(-/-) mice. Moreover, low TUG1 expression and high level of miR-26a are associated with the endothelial protecting effect of tanshinol.